Automotive control systems - Ulsoy, A. Galip (Cambridge University Press, 2012)
The century old automobile, the preferred mode for personal mobility throughout the developed world, is rapidly becoming a complex electro-mechanical system. Various new electro- mechanical technologies are being added to automobiles to improve operational safety, reduce congestion and energy consumption and minimize environmental impact. This chapter provides an introduction to these trends, as well as a brief overview of the major subsystems of an automobile and a brief overview of the automotive control systems to be described in detail in subsequent chapters"--. "This engineering textbook is designed to introduce advanced control systems for vehicles, including advanced automotive concepts and the next generation of vehicles for ITS. For each automotive control problem considered, the authors emphasize the physics and underlying principles behind the control system concept and design. This is an exciting and rapidly developing field for which many articles and reports exist but no modern unifying text. An extensivelist of references is provided at the end of each chapter for all thetopics covered. It is currently the only textbook, including problems and examples, that that covers and integrates the topics of automotive powertrain control, vehicle control and intelligent transportation systems. The emphasis is on fundamental concepts and methods for automotive control systems, rather than the rapidly changing specific technologies. Many of the text examples, as well as the end-of-chapter problems, require the use of MATLAB and/or SIMULINK